The Implementation of Synodality in the Catholic Church and the Expected Impact on Women’s Issues - Lavictoire, Lynn (Université d'Ottawa | University of Ottawa, 2024)
The XVI Ordinary General Assembly of the Synod of Bishops opened up the possibility of a Church more responsive to the voices of all the faithful through the practical implementation of a continuing synodal process. To investigate the impact of this approach, an evaluation is accomplished through the lens of women’s issues to determine whether the current process is viable and its likely impact on addressing women’s issues. Using the synthesis data generated at every level of the Church, analysis is carried out based on theological expectations and problematic sociological issues. Other sociological pressures are also considered which could impede the synodal process as well as suppress the Church hierarchy’s willingness to address women’s issues. Based on this analysis, the synodal process is expected to be implemented as a permanent part of Church life. However, the full resolution of women’s issues will likely take some time, even generations, to occur.
Keywords: Synod; Synodality; Sensus Fidelium; Women's Ordination; Hierarchy; Catholic Church